Implementasi Putusan No. 27/PhPu.D-VIII/2010 Mengenai Perselisihan hasil Pemilihan umum Kepala Daerah Kabupaten Lamongan - Siahaan, Maruarar (Jurnal Konstitusi, 2011)
The objection of petitioner on the recount results by the Election Commission of Lamongan on the orders  of  the  interlocutory  injunction  of  the  Court  ,was  not examined further and be heard simultaneously with  the  Commission  report on the  implementation  of  interlocutory  injunction  in  a  hearing  open  to the public, and thereafter immediately the Constitutional Court considered    the objection has no juridical value. The final decision then confirmed the Commission’s decision on the result of the recounting. Nonetheless, the function of the interlocutory verdict must be understood as a mechanism to prepare the final verdict. Therefore, the results of the interlocutory  verdict  must  be  heard and examined in a session open  to  the  parties  and  the  public,  to  be  used as the basis for a final decision. The hearing process  before  the  final  verdict has been decide, does not end with the announcement of the interlocutory verdict. Implementation of the Constitutional Court decision on   the district election dispute has been uninhibited, but in one case. Although the number is quantitatively insignificant, it is qualitatively very important as a lesson learned in that the Court is still in need to improve its performance in guarding the consolidation of  democracy.